2020
DOI: 10.1017/s1754470x19000357
|View full text |Cite
|
Sign up to set email alerts
|

Trainee self-assessment of cognitive behaviour therapy competence during and after training

Abstract: Large-scale cognitive behavioural therapy (CBT) training and implementation programmes, such as the pioneering Improving Access to Psychological Therapies (IAPT) initiative in the UK, aim to develop a workforce of competent therapists who can deliver evidence-based interventions skilfully. Self-awareness of competence enables CBT therapists to accurately evaluate their clinical practice and determine professional development needs. The accuracy of self-assessed competence, however, remains unclear when compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Studies showed inconsistent results regarding the relationship between therapists’ professional experience and self-assessment bias (Beale et al, 2020; Jaeken et al, 2017; Loades & Myles, 2016; Parker & Waller, 2015). Our study showed no significant association, with a tendency toward higher self-assessments for trainee psychotherapists in contrast to psychology students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed inconsistent results regarding the relationship between therapists’ professional experience and self-assessment bias (Beale et al, 2020; Jaeken et al, 2017; Loades & Myles, 2016; Parker & Waller, 2015). Our study showed no significant association, with a tendency toward higher self-assessments for trainee psychotherapists in contrast to psychology students.…”
Section: Discussionmentioning
confidence: 99%
“…The Dunning–Kruger effect has since been confirmed in a variety of studies, which showed that mental health professionals tended to overestimate their counseling skills (measured through Skilled Counseling Scale or Cognitive Therapy Scale Revised ) before training. After training, they viewed their skills more critically, which led to accurate estimations (i.e., closer to observer-rated levels of competence) or underestimation of skills (Beale et al, 2020; Lepkowski et al, 2009; Little et al, 2005; Urbani et al, 2002). In a study by Jaeken et al (2017), not all trainees overestimated their skills before training.…”
mentioning
confidence: 99%
“…This is supported by research findings that those objectively rated as the least competent practitioners may demonstrate the greatest over-estimation, as they lack awareness of their own deficiencies (Brosan et al, 2008;Dunning et al, 2003). Consequently, this may result in the clinician failing to recognise a need for training or supervision to improve their practice, and the delivery of less effective or even harmful therapy to their clients (Beale et al, 2020;Brosan et al, 2008;McManus et al, 2012). For less experienced trainees the self-assessment of competency has been more variable.…”
Section: Psychology Training and Cbt: Limitations And Opportunitiesmentioning
confidence: 96%
“…With the wide dissemination of cognitive behavioural therapy (CBT) training, especially with the advent of stepped care initiatives, finding methods for competency-based training is important to ensure delivery of effective services (Beale et al, 2020). While there is considerable research on the theory and application of CBT to the treatment of mental health difficulties (Butler et al, 2006;David and Cristea, 2018), there has, until recently, been little research on how training methods relate to the development of trainees' competence in CBT (Bennett-Levy and Lee, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Self-assessment is a core aspect of reflective practice that allows therapists to manage their own learning and facilitates identification of professional development needs. The ability to accurately self-assess competence is also a meta-competence that can be improved with training and supervisory feedback (Beale et al, 2020;Brosan et al, 2008;Loades and Myles, 2016). Self-assessing competence by rating performance within therapy or role-play sessions may be a useful selfdevelopment strategy, especially when used in combination with objective assessor or supervisory ratings.…”
Section: What Is Cbt Competence?mentioning
confidence: 99%